The Statistical Characteristics and Calculated Values for Air Temperature in Building`S Cladding Design - Kariuk, Alla; Koshlatyi, Oleg; Mishchenko, Roman (International Journal of Engineering and Technology, 2018)
The article demonstrates the methodology and the results of statistical characteristics determination and territorial distribution as well as free air winter temperature calculated values required for the designing the building`s cladding.Daily temperatures of free air have been described by a probabilistic model of quasi-stationary differentiable random process. The expectation function is set by the Fourier series or sequence of monthly temperatures, the standard and asymmetry are determined by the mathematical expectation. The Ordinates Distribution Law is described by a linear combination of Gauss and Gumbel distributions. The frequency structure is determined by the time-constant value of the effective frequency. The required statistical characteristics are determined by the results of systematic measurements of average daily air temperature at 485 observation points inUkraine.The calculated values of winter air temperature are determined by using probabilistic approach with accounting for return period equal to building working life, as well as temperature averaging interval, reflecting building`s cladding thermal inertia. The map of territorial distribution of Ukraine has been created based on free air temperature values and dependencies which can lead to calculated values taking into account given building operating life, temperature averaging interval and altitude in mountainous regions.The developed methodology ensures the possibility of minimal calculated values determination for free air temperatures including all the factors mentioned above, and the suggestions as for introduction of norms enabling accounting for building`s cladding thermal inertia within the building working lifeÂ  when making thermotechnical characteristics calculations.Â Â